“Matera: tales of a city” project: an original multiplatform guide on mobile devices - Eva Pietroni (Virtual Archaeology Review)
Matera città Narrata is a project coordinated by CNR ITABC and financed by the Agency of Tourist Promotion of Basilicata region, aimed at the creation of a digital platform able to support the public before and during the visit of Matera (World Heritage since 1993), providing cultural contents by multiple communicative formats and access possibilities. The main components of the project are: 1) the web site, accessible in remote and adapted also from smartphone, 2) cultural contents and applications for mobile devices (old style mobile phone, smartphone, iPad) with different operative systems. Every user can reach cultural contents in a simple way, choosing the communicative format he prefers and supported by the technology he owns. In this paper we'll describe, more in detail, the applications developed.